2010
DOI: 10.1002/dev.20472
|View full text |Cite
|
Sign up to set email alerts
|

Time windows in retention over the first year‐and‐a‐half of life: Spacing effects

Abstract: The time window construct describes when and how an earlier experience will be enduring. According to the construct, there is a limited period after an event occurs, or time window, in which a second event can retrieve and be integrated with the memory of the first event. The construct also holds that when the integration occurs later in the time window, its effects are more enduring. This study examined the time window construct for session spacing with 6- to 18-month-old human infants. Infants of all ages ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…Hsu (2010) examined how long 6-, 9-, 12-, 15-, and 18-month-old infants retained a memory for an operant task, equivalent to the mobile paradigm, when their second session was completed near the end of their time window. Comparing her data with an earlier study that used the same methodology and completed the second session 24 h after the first (Hartshorn et al, 1998a), Hsu (2010) concluded that for 6-month-old infants completing the second session near the end of the time window resulted in better retention, but for the 9- to 18-month-old infants completing the second session near the end of the time window lead to worse retention than a 24 h space.…”
Section: The Spacing Effect In Skill-related Tasksmentioning
confidence: 99%
See 2 more Smart Citations
“…Hsu (2010) examined how long 6-, 9-, 12-, 15-, and 18-month-old infants retained a memory for an operant task, equivalent to the mobile paradigm, when their second session was completed near the end of their time window. Comparing her data with an earlier study that used the same methodology and completed the second session 24 h after the first (Hartshorn et al, 1998a), Hsu (2010) concluded that for 6-month-old infants completing the second session near the end of the time window resulted in better retention, but for the 9- to 18-month-old infants completing the second session near the end of the time window lead to worse retention than a 24 h space.…”
Section: The Spacing Effect In Skill-related Tasksmentioning
confidence: 99%
“…Hsu (2010) examined how long 6-, 9-, 12-, 15-, and 18-month-old infants retained a memory for an operant task, equivalent to the mobile paradigm, when their second session was completed near the end of their time window. Comparing her data with an earlier study that used the same methodology and completed the second session 24 h after the first (Hartshorn et al, 1998a), Hsu (2010) concluded that for 6-month-old infants completing the second session near the end of the time window resulted in better retention, but for the 9- to 18-month-old infants completing the second session near the end of the time window lead to worse retention than a 24 h space. It is important to note that the 9- to 18-month-old infants successfully retrieved their memory in the second session; thus if Hsu’s (2010) conclusions are correct this calls into question the assumption that more difficult retrievals are always better as suggested by some accounts of the spacing effect (e.g., Bjork and Bjork, 1992; Delaney et al, 2010).…”
Section: The Spacing Effect In Skill-related Tasksmentioning
confidence: 99%
See 1 more Smart Citation
“…But 6-month-olds remember–equally long or longer—an association that they formed between two objects they merely observed together, with no procedure or action involved. In operant tasks, infants of all ages remember at least twice as long if given two sessions instead of one, and their retention is prolonged exponentially–by weeks and even months–if the interval between the two training sessions is increased (Hsu, in press). Even 3-month-olds remember for as long as infants two to three times older, depending on the interval between training sessions.…”
Section: Maturation Of the Explicit Memory System Or Experience?mentioning
confidence: 99%
“…Barr et al (2005) found that doubling the number of sessions in which the target actions were modeled on a puppet extended infants’ deferred imitation from 1 to 7 days at 6 months of age. Similarly, Hsu (in press; Hsu and Rovee-Collier, 2009) found that 6- and 9-month-olds remember an operant contingency twice as long after two sessions as after one. In Experiment 2a, therefore, we determined how long infants could remember the S1–S2 association after only one 1-hr preexposure session instead of two.…”
Section: 3 Experiments 2a: a Single 1-hr Preexposure Sessionmentioning
confidence: 89%